2016
DOI: 10.1556/1886.2016.00010
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Gondii Infection and Depression: A Case—Control Seroprevalence Study

Abstract: We assessed the association of Toxoplasma gondii infection and depression in a sample of psychiatric patients and control subjects without depression. We performed an age- and gender-matched case–control study of 89 patients suffering from depression attended in a public psychiatric hospital in Durango City, Mexico and 356 control subjects without depression from the general population of the same city. Participants were tested for the presence of anti-Toxoplasma IgG and IgM antibodies using enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
(29 reference statements)
4
26
2
Order By: Relevance
“…The results of our study point toward an association between certain cardinal depressive symptoms and anti- T. gondii IgG antibodies, which is consistent with the results of some previous studies in psychiatric patients [26], women Veterans [27] and women evaluated for prenatal depression [28]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study point toward an association between certain cardinal depressive symptoms and anti- T. gondii IgG antibodies, which is consistent with the results of some previous studies in psychiatric patients [26], women Veterans [27] and women evaluated for prenatal depression [28]. …”
Section: Discussionsupporting
confidence: 92%
“…Chronic T. gondii infection has also been associated with depression in psychiatric patients [26], women Veterans [27] and pregnant women [28]. However, several other studies found no association between T. gondii infection and depression [23,2932].…”
Section: Introductionmentioning
confidence: 99%
“…Alvarado-Esquivel et al . 14) found no statistical differences with respect to T. gondii between suicide attempters and normal controls. But, they also reported that higher T. gondii antibody titers were related to the risk of suicidal behavior.…”
Section: Discussionmentioning
confidence: 58%
“… 3 However, individuals who develop toxoplasmosis, the disease caused by T. gondii , may present several well-recognized clinical features: lymphadenopathy, chorioretinitis, and meningoencephalitis. 4 , 5 In addition, infection with T. gondii has been associated with heart disease, 6 , 7 schizophrenia, 8 , 9 depression, 10 , 11 and mixed anxiety and depression. 12 Immunocompromised individuals infected with T. gondii may develop disseminated and life-threatening disease.…”
Section: Introductionmentioning
confidence: 99%